A 21st century advancement for mine hoisting systems: Frictionless non-powered emergency arrestors - E. Pribonic (Canadian Institute of Mining, Metallurgy and Petroleum, 2008)
Failure of a mine material hoist can cause injuries, fatalities and significant infrastructure damage, along with an associated loss of production. Principal causes of hoist accidents are overwind and underwind. Past and present means of arresting hoisting equipment are marginally effective and utilize destructive systems that are not reusable following an arrest. The use of permanent magnet eddy current arrestor technology is proposed; the history and fundamental science of the technology are presented, followed by real world examples and calculations of performance for failsafe, friction-free, instantly reusable eddy current arrestors as applied to stopping a 30-ton ore skip traveling at 16 metres per second. A comparison of existing arrestor types with the eddy current arrestor is included and limitations of the ECA are also discussed.